COVID-19 in Latin America and the Caribbean: the visible face of a health regional cooperation in crisis - Herrero, María Belén (2022)
This article analyzes how the Covid-19 pandemic has been addressed in Latin America and the Caribbean, and how regional integration projects could have contributed to deal more effectively with this situation; it also intends to identify current limitations to advance cooperation efforts within regional integration mechanisms in the health sector. A qualitative methodology was conducted based on research and analysis of secondary data. The existing regional integration mechanisms in LAC have quickly sought to promote initiatives to face the pandemic. However, the results – being fragmented – have not been enough to prepare, through regional integration, more effective responses to Covid-19.